2016
DOI: 10.1016/j.bbmt.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Mogamulizumab Treatment Prior to Allogeneic Hematopoietic Stem Cell Transplantation Induces Severe Acute Graft-versus-Host Disease

Abstract: Mogamulizumab (MOG), a humanized anti-CC chemokine receptor 4 (CCR4) monoclonal antibody, has recently played an important role in the treatment of adult T cell leukemia/lymphoma (ATLL). Because CCR4 is expressed on normal regulatory T cells as well as on ATLL cells, MOG may accelerate graft-versus-host disease (GVHD) by eradicating regulatory T cells in patients with allogeneic hematopoietic stem cell transplantation (allo-HSCT). However, there is limited information about its safety and efficacy in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…The Fukuoka BMT group retrospectively compared the clinical outcome of patients who did or did not receive Moga before allo‐HSCT (n = 25 and 105, respectively) . In this cohort, the use of Moga significantly improved the disease status before allo‐HSCT, but the incidence of NRM at 1 year after allo‐HSCT was higher, although not significantly so, in patients who received Moga than in those who did not (49.0% vs 27.9%, P = .06).…”
Section: Presentation Of Case Series Of Patients Who Received Mogamulmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fukuoka BMT group retrospectively compared the clinical outcome of patients who did or did not receive Moga before allo‐HSCT (n = 25 and 105, respectively) . In this cohort, the use of Moga significantly improved the disease status before allo‐HSCT, but the incidence of NRM at 1 year after allo‐HSCT was higher, although not significantly so, in patients who received Moga than in those who did not (49.0% vs 27.9%, P = .06).…”
Section: Presentation Of Case Series Of Patients Who Received Mogamulmentioning
confidence: 99%
“…In a retrospective analysis of a database from the Fukuoka BMT group, an interval shorter than 80 days between the last Moga dose and allo‐HSCT was associated with a higher incidence of grade III‐IV acute GVHD than an interval of 80 days or longer …”
Section: Key Scientific Statement To the Clinical Questions Regardingmentioning
confidence: 99%
“…Recently, several groups reported the clinical outcomes of cases that received moga before allo-HSCT. These studies consistently reported that the use of moga before allo-HSCT was associated with an increased risk of severe acute GVHD (43)(44)(45)(46), although a case report showed the successful management of acute GVHD (45). However, these studies were rather small to conduct multivariate analyses to adjust for the other risk factors of acute GVHD and other clinical events.…”
Section: Foxp3mentioning
confidence: 99%
“…Using 50 days as a cut-off, a shorter interval between the last moga administration and allo-HSCT was significantly associated with an increased risk of non-relapse mortality and overall mortality. Sugio et al suggested that an interval of <3 months between the last moga administration and allo-HSCT might be associated with an inferior clinical outcome (46). According to some previous reports, the concentration of moga remains more than 10 μg/mL for weeks even after the last administration of 1.0 mg/kg (25).…”
Section: Foxp3mentioning
confidence: 99%
“…Anti-CCR4 monoclonal antibody mogamulizumab (Mog) is the first immunotherapeutic agent targeting ATLL. Since CCR4 is expressed on regulatory T cells (Treg), there is growing concern regarding increased risk of severe and refractory acute graft-versus-host disease (aGVHD) in ATLL patients treated with Mog before allo-HSCT (pretransplant Mog) [36]. …”
mentioning
confidence: 99%